2018
DOI: 10.1128/aem.00868-18
|View full text |Cite
|
Sign up to set email alerts
|

Sheep as a Potential Source of Zoonotic Cryptosporidiosis in China

Abstract: In this study, we assessed the prevalence and genetic characteristics of in sheep from 10 provinces in China. Fecal samples from 1,035 sheep originating from 16 farms were collected, and 295 (28.5%) were found to be positive by nested PCR. was detected at all farms, with infection rates between 5.7% and 50.0%. Three species were identified, including (73.2%, 216/295), (21.7%, 64/295), and (5.1%, 15/295). The distribution of species differed by province and by farm. All three species were detected in lambs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 61 publications
4
24
3
Order By: Relevance
“…The IIdA18G1 subtype appeared mainly represented in the region of “Occitanie” where sheep farming is dominant. It is coherent with the literature since this subtype has already been described in sheep and lambs [ 46 , 47 ]. Not surprisingly, the anthroponotic C. hominis IbA10G2 subtype was mainly reported; this subtype is known as the worldwide dominant C. hominis subtype [ 7 , 20 , 28 , 48 ].…”
Section: Discussionsupporting
confidence: 90%
“…The IIdA18G1 subtype appeared mainly represented in the region of “Occitanie” where sheep farming is dominant. It is coherent with the literature since this subtype has already been described in sheep and lambs [ 46 , 47 ]. Not surprisingly, the anthroponotic C. hominis IbA10G2 subtype was mainly reported; this subtype is known as the worldwide dominant C. hominis subtype [ 7 , 20 , 28 , 48 ].…”
Section: Discussionsupporting
confidence: 90%
“…The overall prevalence of Cryptosporidium infection found in this study (10.1%) is higher than that reported in Spain (5.9%; Díaz et al, 2018a ) and lower than most investigations worldwide, which have reported infection rates ranging from 14 to 29% (Holsback et al, 2018 , Mi et al, 2018 , Chikweto et al, 2019 , Khan et al, 2019 ). A prevalence higher than 50% has also been recorded (Bhat et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 64%
“…The two Cryptosporidium species identified in lambs from Sardinia, C. parvum and C. ubiquitum , are considered the most common species in sheep together with C. xiaoi (Ye et al, 2013 , Tzanidakis et al, 2014 , Li et al, 2016 , Baroudi et al, 2018 , Díaz et al, 2018a , Mi et al, 2018 , Mammeri et al, 2019 , Qi et al, 2019 , Rabee et al, 2020 , Santín, 2020). Our results are in agreement with most investigations reporting C. parvum as the main species in pre-weaned lambs (Castro-Hermida et al, 2007 , Paoletti et al, 2009 ,Tzanidakis et al, 2014 ) and especially in those presenting diarrhoea (Mueller-Doblies et al, 2008 , Quílez et al, 2008 , Díaz et al, 2010 , 2015 , Papanikolopoulou et al, 2018 , Mammeri et al, 2019 , Kabir et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study identified the exclusive occurrence of a few IIa subtypes in yak, including IIaA15G2R1 (n: 8), IIaA16G2R1 (n: 2), IIaA14G1R1 (n: 1), IIaA14G2R1 (n: 1) and IIaA16G3R1 (n: 1) ( 80 ). The IIa subtypes identified in sheep include IIaA15G2R1 and IIaA17G2R1 ( 81 ), and those identified in goats include IIaA14G2R1, IIaA15G1R1, IIaA15G2R1 and IIaA17G2R1 ( 82 ). Of these seven IIa subtypes identified in yak, sheep, and goats in China, only subtypes IIaA15G2R1 and IIaA17G2R1 were identified in calves in Uruguay.…”
Section: Discussionmentioning
confidence: 99%